Temperature strongly correlates with regional patterns of body size variation in Mediterranean small pelagic fish species - HATTAB, TAREK; GUCU, ALI; VENTERO, ANA; De FELICE, ANDREA; MACHIAS, ATHANASSIOS; SARAUX, CLAIRE; GAŠPAREVIĆ, DENIS; BASILONE, GUALTIERO; COSTANTINI, ILARIA; LEONORI, IOLE; BOURDEIX, JEAN-HERVÉ; IGLESIAS, MAGDALENA; et al. (Mediterranean Marine Science, 2021)
In this study, we consider the applicability of Bergmann’s rule to the populations of small pelagic fish species in the Mediterranean Sea. Under Bergmann’s rule, body size increases with decreasing temperature and increasing latitude. Although this macroecological pattern in body sizes is well established for many taxa of endotherms and ectotherms, it remains not universal and the proposed mechanisms underlying it are multiple and still lack consensus. We explored here the occurrence of geographical body size clines using measurements of average body sizes of 10 species collected in pelagic trawl hauls carried out during acoustic surveys in the Mediterranean Sea. Bergmann’s rule was evaluated by correlating body sizes with latitude and temperature for each species while accounting for potential confounding variables and sampling bias. For 5 species, namely anchovy, sardine, Atlantic chub mackerel, bogue, and blue jack mackerel, we demonstrate that they follow a Bergmann’s rule, with a decline in average body size by about 3.01, 3.43, 3.67, 3.82, and 3.76 % per 1°C of warming respectively, although this did not translate with an increase in size with latitude. The adherence of these 5 pelagic fish to Bergmann’s rules strongly suggests that temperature is a major determinant of their body sizes and enables them to act as sentinel species for identifying the drivers and consequences of warming in the Mediterranean ecosystems.